SYMBOLIZING VALUE OF NAMES OF ANIMALS AND NUMBERS IN THE KAZAKH PROVERBS AND SAYINGS - Esirkepova, K. K.; Kanapina, S.G.; Bekbossynova, А.Kh. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
A symbol is a phenomenon characterzed for any culture. The symbol can have different meanings and codes in the context of different cultures. The article reveals the symbolic meaning of animals and numerals in the national world-view.
Keywords: National world-view; the symbolic meaning of animals; the symbolism of numerals; national culture